2001
DOI: 10.1590/s0037-86822001000600008
|View full text |Cite
|
Sign up to set email alerts
|

Perfil soroepidemiológico da infecção pelo vírus da hepatite B em profissionais das unidades de hemodiálise de Goiânia-Goiás, Brasil Central

Abstract: Resumo Para investigar o perfil da infecção pelo vírus da hepatite B (VHB) em profissionais de hemodiálise (N=152) de Goiânia, Goiás, amostras sangüíneas foram testadas para detecção dos marcadores: AgHBs, anti-HBs e anti-HBc. Uma prevalência global de 24,3% (IC 95%: 17, Abstract In order to investigate the hepatitis B virus (HBV) infection profile in hemodialysis staff (n = 152) of Goiânia,Goiás, blood samples were tested for detection of HBsAg, anti-HBs and anti-HBc markers. An overall HBV infection prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
10

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
2
6
0
10
Order By: Relevance
“…Corroborating other studies (Ferraz et al 1992, Oliveira 1997, Cuevas et al 1997, Turchi et al 1997, Arca et al 1998, Lopes et al 2001, we observed that the vaccine response index was significantly higher among dentists who received the third dose up to one year before the interview, compared to their counterparts. a: the samples 1-3 were HBsAg/anti-HBc/anti-HBe positive; the samples 5-9 were anti-HBc/anti-HBs positive.…”
Section: Discussionsupporting
confidence: 88%
“…Corroborating other studies (Ferraz et al 1992, Oliveira 1997, Cuevas et al 1997, Turchi et al 1997, Arca et al 1998, Lopes et al 2001, we observed that the vaccine response index was significantly higher among dentists who received the third dose up to one year before the interview, compared to their counterparts. a: the samples 1-3 were HBsAg/anti-HBc/anti-HBe positive; the samples 5-9 were anti-HBc/anti-HBs positive.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies related to HBV have been carried out in Goiânia, Goiás in the general population and in risk groups, and it was observed that the rate of seroprevalence varies from 6.1% -urban female population (8) to 63.4% -dialysis center patients (4). In addition, studies from different groups of HCWs, found a seroprevalence of 23.4% in hospital workers (1), 23.1% in workers at hemodialysis centers (15) and 24.1% in laboratory workers (20). However, there are no studies regarding the hepatitis B infection in dentists.…”
Section: Introductionmentioning
confidence: 99%
“…Dados registrados na literatura alertam para o risco de infecção ocupacional cujos agentes são veiculados pelo sangue e outros fluídos corpóreos, apontam ainda a maior infectividade do VHB em relação ao HIV, entre os profissionais da área da saúde e atingindo um percentual de suscetibilidade maior em relação à população em geral (1,16,17) .…”
Section: Resultsunclassified